2020
DOI: 10.1155/2020/8854412
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Transcranial Direct Current Stimulation (tDCS) in the Normalization of Brain Activation in Patients with Neuropsychiatric Disorders: A Systematic Review of Neurophysiological and Neuroimaging Studies

Abstract: Background. People with neuropsychiatric disorders have been found to have abnormal brain activity, which is associated with the persistent functional impairment found in these patients. Recently, transcranial direct current stimulation (tDCS) has been shown to normalize this pathological brain activity, although the results are inconsistent. Objective. We explored whether tDCS alters and normalizes brain activity among patients with neuropsychiatric disorders. Moreover, we examined whether these changes in br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 94 publications
0
3
0
Order By: Relevance
“…Using tDCS with the anodes and cathodes on F3 and F4 electrodes can improve the cognitive ability of individuals with cognitive impairment after stroke (20) and change their cortical excitability (21). In animal studies (22,23), direct currents have been shown to change brain excitability.…”
Section: Introductionmentioning
confidence: 99%
“…Using tDCS with the anodes and cathodes on F3 and F4 electrodes can improve the cognitive ability of individuals with cognitive impairment after stroke (20) and change their cortical excitability (21). In animal studies (22,23), direct currents have been shown to change brain excitability.…”
Section: Introductionmentioning
confidence: 99%
“…Therapeutically, tDCS is used to alter local neuronal excitability that is assumed to be in a dysfunctional hypo- or hyperactive state ( 45 ). Effects of the stimulation expand by changes in the neural network into more distant regions and lead to reorganization of neuronal circuits ( 45 , 57 ). Due to encouraging results in the treatment of various neuropsychiatric disorders in adults ( 58 61 ), tDCS has gained attention in the treatment of childhood and adolescent neuropsychiatric disorders over the past years ( 45 , 62 64 ).…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review of neuropsychological and neuroimaging studies of patients with neuropsychiatric disorders, reported that the clinical effect of tDCS is closely linked with symptom severity 31 . This finding suggests that when the symptoms are more severe (in the acute phase), choosing tDCS as early augmentation strategy may help reduce the symptoms.…”
mentioning
confidence: 99%